A sacred commitment: How rituals promote group survival. (August 2021) - Stein, Daniel H; Hobson, Nicholas M; Schroeder, Juliana
Highlights: Rituals are meaningful actions marked by rigidity, formality, and repetition. Group rituals promote cognitive, affective, and behavioral group commitment. Group rituals not only signal commitment (external) but enhance it internally. In so doing, rituals contribute to the survival of religious groups. Abstract : Religious groups have survived for thousands of years despite drastic changes in society. One reason for their successful survival is the proliferation of group rituals (i.e. meaningful sequences of actions characterized by rigidity, formality, and repetition). We propose that rituals enhance religious group survival not only by signaling external commitment but also by fostering internal commitment toward the group in three ways: (1) enhancing belief in the group's values ('committed cognition'), (2) increasing the desire to maintain membership in the group ('committed affect'), and (3) increasing contributions to the welfare of the group ('committed behavior'). We conclude with a call for new empirical research on how participating in rituals can enhance internal commitment toward one's group (116/120).